Adsorption of strontium (II) metal ions using phosphonate-functionalized polymer - Bhosle, S. M.; Ponrathnam, S.; Tambe, S. S.; Chavan, N. N. (Bulletin of Materials Science, 2016)
Diethyl[3-(methoxydimethylsilyl)propyl]phosphonate (DMPP) polymer was synthesized for the strontium (II) metal ion recovery using diethylallylphosphonate as staring material. Diethylallylphosphonate was reacted with poly(methylhydro)siloxane (MW 1900-2000 g mol (-1) ) in the presence of Speier's catalyst. The synthesized monomer was characterized by IR, (1) H NMR, (1 3) C NMR and FT-IR spectroscopy techniques, and the synthesized polymers were characterized by IR and NMR spectroscopy, differential scanning calorimetry, thermogravimetric analysis and solubility. The synthesized polymer was used for sequestering strontium metal from the aqueous solution. The metal binding was examined by the energy dispersive spectroscopy and scanning electron microscopy for the adsorbed Sr(II). Batch adsorption studies were performed by varying three parameters, namely initial pH, adsorbent dose and the contact time. The reaction kinetics was determined by the Langmuir, Freundlich, and pseudo-first- and second-order models. Results of this study indicate that the synthesized polymer DMPP has been effective in removing Sr(II) from the aqueous solution.